The effect of germination of the physico-chemical properties of black gram (Vigna mungo L.) - Ghazali, H.M; Cheng, S.C (1991)
Rehydration of dry black gram seeds activated metabolic processes that caused changes in the chemical composition and allowed growth of the seeds. Further changes were recorded when germination occurred and the components that were found to be affected were the protein, fat, vitamin C, total carotenoid (provitamin A) and simple sugar (glucose, fructose and sucrose) contents. The protein and fat contents decreased following germination. Vitamin C content, on the other hand, increased significantly when seeds were soaked and allowed to germinate. Although higher in value than the dry seeds, the vitamin C content decreased after germination for 1 day. The total carotenoid content of dry seeds was higher than either the soaked seeds or the sprouts. Soaking caused a substantial loss in total carotenoid but the content slowly increased upon germination. Sucrose was the major simple sugar of dry seeds. Upon imbibition of water, glucose and fructose were completely lost. Germination led to an increase in the contents of all three sugars. © 1991.